KEKUATAN MEDIA SOSIAL DALAM KEMENANGAN POLITIK - Andi Ardiansyah (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2014)
It is argued that media have great impact on human beings. Mass communication was able to persuade the public from cognitive (knowledge) and affective aspects (emotional and feeling) to changes in behavior. These effects are related to each other. This is due to the fact that when people receive messages, they do not immediately accept it, but the messages are filtered with careful consideration. And there are still personal and social factors which determine the extent to which mass media have impacts on changes in human attitudes and behavior. Indeed, humans live in a world that is filled with a variety of needs and interests, in which the media has a big role. The people’s actions may not directly result from the influence of the media. However, it cannot be denied that the global community will increasingly depend on the media.